Influence of Student Behavior on Hepatitis A Incidence and Prevalence in Islamic Boarding School âSidogiriâ - Secaria, Bhirawa Odie Prino; Sulistyorini, Lilis; Keman, Soedjajadi (Health Notions, 2018)
abstract